Integrated care and fall prevention in active and healthy aging - Eklund, Patrik (Advances in medical diagnosis, treatment, and care (AMDTC) book series., 2021)
"This book provides relevant theoretical and practical frameworks in the area of falls prevention and is written for professionals who want to improve their understanding of the strategic role of falls prevention as one of the major societal challenges within active and healthy ageing"--